Thermodynamic and structural properties of K-Na liquid alloy - Koirala, I; Jha, IS; Singh, BP (BIBECHANA, 2012)
The deviation from ideal mixture behavior and concentration dependent symmetry in thermodynamic and structural properties of K-Na liquid alloy is investigated within a simple statistical model. The concentration dependence of the free energy of mixing, heat of mixing, entropy of mixing, concentration fluctuation in the long wavelength limit, Warren-Cowley short range order parameter, ratio of diffusion coefficients of Potassium-sodium alloy at 384 K and activity of the components has got special attention to show a tendency of like atom pairing in the mixture. DOI: http://dx.doi.org/10.3126/bibechana.v9i0.7187 BIBECHANA 9 (2013) 130-135